On modelling digital healthcare ecosystems and their knowledge management - Nimmagadda, Shastri; Reiners, Torsten; Wood, Lincoln; Chitti, S.K. (2019)
© 2019 Association for Information Systems. All rights reserved. The Human Anatomy, Physiology and Psychology Integrated Egghead Relationships (HAPPIER) are embedded domains of a human ecosystem. In the digital ecosystem perspective, the idiom “Integrated-Egghead-Relationships” describes composite domains with encapsulation of multiple data attribute dimensions. The increase in physiological and psychological disorders among the mass population in periodic and geographic dimensions has reported an outburst of volumes and varieties of data in healthcare ecosystems. The data heterogeneity and multidimensionality are other challenges constraining the data integration process, at times disconnecting patients and medical practitioners. Knowledge-based data models are needed to manage unstructured cognitive healthcare Big Data. The purpose of the research is to build a framework and integrate multilayered models in multidimensional warehouse repository. The integrated framework can engage multiple scopes of HAPPIER and collaborate with human cognitive anatomy and physiological data events in large-scale depositories. The repositories can bring values in new knowledge domains, making healthcare projects operationally successful.